Effects of concentration and synergism on drug solubilising behaviour of PVP K 30 and PEG 6000 (Jahangirnagar University Journal of Biological Sciences, 2016)
The effect of concentration and synergism on drug solubilising behaviour of PVP K 30 and PEG 6000 were investigated. Our results showed that amount of drug solubilised by the surfactants decreased as surfactant concentration was increased. Regarding the effect of synergism of the two surfactants on drug solubilisation our results failed to show synergism. The amount of drug solubilised by a single surfactant did not differ much when combination of surfactants were used.Jahangirnagar University J. Biol. Sci. 3(2): 49-55, 2014 (December)